Structural Analysis of Multi-Helical RNAs by NMR–SAXS/WAXS: Application to the U4/U6 di-snRNA. Issue 5 (27th February 2016) - Cornilescu, Gabriel; Didychuk, Allison L.; Rodgers, Margaret L.; Michael, Lauren A.; Burke, Jordan E.; Montemayor, Eric J.; Hoskins, Aaron A.; Butcher, Samuel E.
Abstract: NMR and SAXS ( s mall- a ngle X -ray s cattering)/WAXS ( w ide- a ngle X -ray s cattering) are highly complementary approaches for the analysis of RNA structure in solution. Here we describe an efficient NMR–SAXS/WAXS approach for structural investigation of multi-helical RNAs. We illustrate this approach by determining the overall fold of a 92-nt 3-helix junction from the U4/U6 di-snRNA. The U4/U6 di-snRNA is conserved in eukaryotes and is part of the U4/U6.U5 tri-snRNP, a large ribonucleoprotein complex that comprises a major subunit of the assembled spliceosome. Helical orientations can be determined by X-ray scattering data alone, but the addition of NMR RDC ( r esidual d ipolar c oupling) restraints improves the structure models. RDCs were measured in two different external alignment media and also by magnetic susceptibility anisotropy. The resulting alignment tensors are collinear, which is a previously noted problem for nucleic acids. Including WAXS data in the calculations produces models with significantly better fits to the scattering data. In solution, the U4/U6 di-snRNA forms a 3-helix junction with a planar Y-shaped structure and has no detectable tertiary interactions. Single-molecule Förster resonance energy transfer data support the observed topology. A comparison with the recently determined cryo-electron microscopy structure of the U4/U6.U5 tri-snRNP illustrates how proteins scaffold the RNA and dramatically alter the geometry of the U4/U6 3-helix junction. Graphical abstract: Highlights: A method is described for modeling RNA structures from NMR–SAXS/WAXS data. Inclusion of WAXS data significantly improves agreement with experimental data. Application to a 92-nt U4/U6 3-helix junction RNA is illustrated.